Normativity and redundancy in the modern Ukrainian language - Сухенко, Вікторія Григорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
In the article the concept of redundancy in the Ukrainian language is analyzed. The use of words without taking into account their meaning is the most common violation of this requirement. The inability of the speaker to express his opinion accurately appears in such a defect as speech excess. However, it can be useful, as it promotes expression and eliminates "obstacles" in perceptions of information, makes it possible to clarify it. The cognitive approach has allowed to reveal a positive connotation of the investigated phenomenon, to consider it as a source of expressiveness, imagery and the emotionality of language means. The analyzed phenomenon of redundancy in the Ukrainian language is considered as an unintentional repetition of linguistic units, as a functional tautology and as a normative redundancy. The article focuses on such manifestations of redundancy as tautology and pleonasm, emphasizing their difference. The reasons and functional features of redundancy are also disclosed, cases of its use in oral and written speech are considered, the results of observations are generalized.